The impact of air pollution on cross section anatomical characteristics Of Pinus eldarica wood - Vahid reza ُSafdari (Regional Information Center for Science and Technology (RICeST), 2012)
Air pollutantion in particular pollutants from automobile exhaust can affect anatomical and morphological characteristics of woods.  In order to investigate the impact of this factor, Pinus eldarica trees of Chitgar park in Tehran, the area which is extended from south to crowded highway (polluted site) and in north to Alborz Mountain (unpolluted site) and the middle part (semi-polluted site) were sampled by increment borer. After cross-dating, the tree rings of recent 5 years were separated from the old rings. Then anatomical characteristics of cross section, including transition between early and latewood, tangential thickness of last formed latewood tracheides, frequency of ray and resin ducts and morphological characteristics of tracheids in three zones and in the same rings were studied. Results indicated that the ring width pattern of Pinus eldarica in three zones is somehow the same. The frequency of resin duct and rays and false rings in 2005 and 2006 in the polluted and semi-polluted site were higher compare to the unpolluted site. Fiber length, wall thickness (2d) and lumen size of trees of unpolluted site were more than the other two sites (Polluted and Semi-polluted). In general, it could be concluded that air pollution impact on tree ring width can reduce wood quality as well.